A phenomenology study of dhikr spiritual meditation practice among recovering drug abusers - Rozeeda Kadri; Syamsul Azizul Marinsah; Muammar Arafat Yusmad (Penerbit UPM, 2025)
Spirituality and religiosity-based interventions have emerged as powerful platforms within substance use recovery and research. In particular, the incorporation of meditation is becoming crucial. However, dhikr, as one of the pivotal meditation practices in Islam, has yet to be fully understood. The present article aimed to explore the experiences of dhikr meditation practice among recovering drug addicts. The study utilized a phenomenological qualitative study design with face-to-face, semi-structured interviews. A total of six participants, comprising recovering drug addicts who had been in the Islamic rehabilitation program that practiced dhikr spiritual meditation for at least two years, were interviewed in this study. The interviews were audio recorded and transcribed verbatim. Then, the data were analyzed using thematic analysis for qualitative analysis. Four meanings emerged based on the participants’ experience, namely “Redemption and Salvation,” “Spiritual Journey,” “Vow to God,” and “Reliance and Togetherness.” The findings revealed that the intertwined relationship between dhikr spiritual meditation and religiosity worldview has provided a powerful philosophy and cognitive framework that helps drug addicts’ recovery and maintains abstinence. The study implies that the Islamic context in dhikr spiritual practice is fundamental in the recovery process. Further study on addiction treatment is suggested, with a focus on the dhikr meditation and spirituality module.